Uncertainty and investment in precision agriculture - Is it worth the money? - Tozer, Peter (International Conference on Precision Agriculture ICPA, 2008)
Irreversibility and uncertainty render the standard capital budgeting techniques such as net present value (NPV) analysis insufficient as a decision criterion. The standard NPV underestimates the value of the investment by not including the value of waiting for new information to reduce the uncertainty of the cashflows generated by the investment. An alternative to NPV analysis is real options. In this study we apply real options analysis to an investment decision for a grain producer in Western Australia. The investment choice is to purchase machinery suitable for undertaking controlled traffic precision agriculture or acquire a conventional system and reduce sowing time. The results of the analysis suggest that the required rates of return for the two investment alternatives need to be approximately 20-40 % higher than the returns estimated by the standard NPV analysis. These higher rates of return are required to compensate for the uncertainty inherent in the cropping systems of the farm. Also, in most cases, even though the variable costs of operating the precision agriculture system were higher, due to smaller operating widths, the additional returns generated by managing zones individually outweighed these additional costs. Further analysis also shows that the relative size of management zones has a marked effect on the returns generated and that it is possible to increase returns by taking out marginally productive zones.